Breast Regional Anesthesia Practice in the Italian Public Health System (BRA-SURVEY): A Survey-Based National Study. (7th June 2021) - Bonvicini, Daniele; De Cassai, Alessandro; Andreatta, Giulio; Salvagno, Michele; Carbonari, Ilaria; Carere, Anna; Fornasier, Marcello; Iori, Davide; Negrello, Michele; Grutta, Giuseppe; Navalesi, Paolo
Abstract : BACKGROUND: Breast cancer is the most common malignancy in women. Surgery is a mainstay therapy unfortunately burdened by complications as severe postoperative pain. Regional anesthesia may play a role in a multimodal strategy for prevention and treatment of postoperative pain. The main purpose of this survey was to investigate the rate of use of regional anesthesia techniques in patients undergoing breast surgery in the Italian public hospital system. METHODS: We designed an online survey that consisted of 22 questions investigating the anesthesia management of breast surgery, particularly focused on regional anesthesia. The survey lasted from November 18, 2019 to February 28, 2020. Directors of anesthesia departments of 168 Italian public health system hospitals were contacted and invited to forward the survey to every anesthesiologist in their unit. RESULTS: A total of 935 anesthesiologists received the survey; among them 460 entered the final analysis. Regional anesthesia was not used by 44.6% of the anesthesiologists and lack of experience/training was the main cause (75.6%). Logistic regression models revealed that anesthesiologists with more than 15 years of experience (odds ratio [OR] = 0.55; 95% confidence interval [CI], 0.33–0.93) or working most of their days in intensive care unit (ICU) compared to operating theater (OR = 0.25; 95% CI, 0.14–0.43) were less likely to perform regional anesthesia techniques. CONCLUSIONS: Low implementation of regional anesthesia techniques in breast surgery emerges from our survey and the major reason cited is a lack of proper training. An improved training program in regional anesthesia, especially in residents' curricula, could be useful to increase its rate of use and to standardize its practice.